Laser-based Mass Spectrometry for the Identification of Potential Biomarkers and Habitability Indicators on Polygon Structures - Luca N. Knecht; Salome Gruchola; Charles S. Cockell; Scott M. Perl; Mary Beth Wilhelm; Peter Keresztes Schmidt; Coenraad P. de Koning; Marek Tulej; Nicolas Thomas; Peter Wurz; Andreas Riedo (The Planetary Science Journal, 2025)
Polygonal structures, some of which are formed in salt deposits, have been documented at numerous locations on the surface of Mars, clearly visible from orbit with high-resolution imaging systems and spectral techniques. Based on a terrestrial analog, these deposits are potential locations to harbor biomarkers, which play a key role in the search for extraterrestrial life. This study examines the measurement capabilities of a laser-based mass spectrometer for the chemical composition analysis of such polygonal structures found in the Boulby Mine, United Kingdom, a Mars analog site. A space-prototype laser ablation ionization mass spectrometry system was used to measure the elemental composition of the material. The analysis for potentially habitable conditions and the presence of preserved biomarkers is based on the abundance of the CHNOPS elements in the halite host. In total, six samples, three from the edge and interior, respectively, of various polygons were investigated. The chemical analysis showed that the edges of polygonal structured salt deposits are preferential sites for element accumulation, with a higher abundance in CHNOPS elements and other trace elements necessary for the formation and maintenance of life. Polygonal structures might be alternative landing sites for future in situ space exploration missions devoted to life detection. The availability and ability to interpret imaging data from orbit enable an easy targeting of polygon structures, thus improving the selection for a landing site with higher potential to detect biosignatures and reducing mission costs by deploying dedicated instrumentation for in situ analysis.